Measurement of the production cross section for W -bosons in association with jets in pp collisions at √s = 7 TeV with the ATLAS detector - Anduaga, Xabier Sebastián (2011)
This Letter reports on a first measurement of the inclusive W + jets cross section in proton–proton collisions at a centre-of-mass energy of 7 TeV at the LHC, with the ATLAS detector. Cross sections, in both the electron and muon decay modes of the W -boson, are presented as a function of jet multiplicity and of the transverse momentum of the leading and next-to-leading jets in the event. Measurements are also presented of the ratio of cross sections σ(W + ≥ n)/σ(W + ≥ n − 1) for inclusive jet multiplicities n = 1–4. The results, based on an integrated luminosity of 1.3 pb−1, have been corrected for all known detector effects and are quoted in a limited and well-defined range of jet and lepton kinematics. The measured cross sections are compared to particle-level predictions based on perturbative QCD. Next-to- leading order calculations, studied here for n ≤ 2, are found in good agreement with the data. Leading- order multiparton event generators, normalized to the NNLO total cross section, describe the data well for all measured jet multiplicities.